Isolating Effects of Temperature and Light on Nutrient Acquisition by Biofilm and Bryophyte Communities in Arctic Spring-Stream Ecosystems - Tori A. Hebert; Adam C. Hensley; Carla L. Atkinson; Jonathan P. Benstead; Alexander D. Huryn (Ecosystems, 2026)

Environmental gradients drive convergence in life history strategies among disparate but coevolved taxonomic groups - Carla L. Atkinson; Alex J. Franzen; Garrett W. Hopper; Jonathan W. Lopez; Zachery D. Zbinden; Caryn C. Vaughn (Ecology, 2025)
Trait‐based approaches can improve ecological understanding by linking fitness to the environment. The trilateral life history model is an expansion of r‐ and K‐selection theory that reflects trade‐offs between juvenile survival, fecundity, and generation time and describes differential survival of species across environmental gradients. We used this framework to generate and test hypotheses regarding community assembly and the validity of such a model in two disparate taxonomic groups, freshwater mussels and fish. We assessed the distribution of mussel and fish life history strategies across 80 sites spanning aspects of the river continuum concept within the Ouachita Highlands (USA) and asked if their distributions are predicted by a similar life history strategy framework. Because mussel and fish assemblages should both be structured by selective forces in an up‐ to downstream trajectory, we expected both taxa to converge on more species‐rich assemblages with a greater proportion of equilibrium strategists in larger, more stable downstream habitats. We found that both mussel and fish species richness increased with watershed area as well as the proportion of equilibrium strategists in the assemblages. Our study validates the use of the trilateral life history model to test hypotheses about the distribution patterns of two coevolved taxonomic groups.

Establishing a basis for recognising marine ‘other effective area-based conservation measures’ (OECMs) in South Africa - SP Kirkman; P Kowalski; SD Holness; LJ Atkinson; R Brand; L Dunga; TP Fairweather; T Goldman; D Marnewick; J Nhleko; R Peter; C Smith; et al. (African Journal of Marine Science, 2025)

A global meta‐analysis of ecological functions and regulating ecosystem services of freshwater bivalves - Alexandra Zieritz; Joshua I. Brian; Ronaldo Sousa; David C. Aldridge; Carla L. Atkinson; Karel Douda; Caryn Vaughn; Yulia Bespalaya; Tabitha Richmond; Adam M. Ćmiel; Alma Crisp; Andreas H. Dobler; et al. (Limnology and Oceanography, 2025)
Freshwater bivalves are globally distributed, diverse, and common in benthic communities. Many taxa, particularly in the most species‐rich order, Unionida, are declining due to anthropogenic stressors, while a small number of non‐native species have become increasingly abundant and widespread, commonly replacing native bivalve assemblages. To understand how these global changes may impact ecosystems and people, we conducted a meta‐analysis of existing literature quantifying the ecological functions (= supporting or intermediate ecosystem services) and regulating ecosystem services of freshwater bivalves (hereafter “ecosystem services”). Random effects meta‐analysis modeling across 447 case studies revealed a positive effect on human health, safety, or comfort of freshwater bivalve ecosystem services overall and specifically, via effects on native macrofauna, microorganisms, wastes, and pollutants, and the physico‐chemical condition or quantity of sediments. Generally, effects of native species and species within the orders Unionida and Venerida were more significant and positive than those of other freshwater bivalves. No significant overall effect was found for ecosystem services related to zooplankton, algae, invasive species, and the physico‐chemical condition of ambient water. Moreover, a significant bias toward publication of positive results existed for studies quantifying ecosystem services related to algae. These findings illustrate the global importance of the ecosystem services of freshwater bivalves and highlight the need for large‐scale conservation and restoration efforts for their species and populations globally, including those of common species. Our findings also question common assumptions of strong and ubiquitous effects of freshwater bivalves on algae and water condition, cautioning against extrapolating observations across systems.

Causes and consequences of long-term defaunation in multi-species aggregations: species traits predict freshwater mussel declines and decreases in biogeochemical storage and recycling - Jonathan W. Lopez; Carla L. Atkinson; Caryn C. Vaughn (Oecologia, 2025)

Integration of genetic, taxonomic, and functional dimensions of biodiversity yields conservation insights - Carla L. Atkinson; Irene Sánchez González; Jamie R. Bucholz; Garrett W. Hopper; Ryan C. Garrick; Colin R. Jackson; Jeffrey D. Lozier (Biological Conservation, 2025)

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Herbal leys have no effect on soil porosity, earthworm abundance, and microbial community composition compared to a grass-clover ley in a sheep grazed grassland after 2-years - Emily C. Cooledge; Craig J. Sturrock; Brian S. Atkinson; Sacha J. Mooney; Francesca L. Brailsford; Daniel V. Murphy; Jonathan R. Leake; David R. Chadwick; Davey L. Jones (Agriculture, Ecosystems & Environment, 2024)

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

Community‐wide correlations between species richness, abundance and population genomic diversity in a freshwater biodiversity hotspot - Jamie R. Bucholz; Garrett W. Hopper; Irene Sánchez González; Taylor E. Kelley; Colin R. Jackson; Ryan C. Garrick; Carla L. Atkinson; Jeffrey D. Lozier (Molecular Ecology, 2023)
Understanding patterns of diversity across macro (e.g. species‐level) and micro (e.g. molecular‐level) scales can shed light on community function and stability by elucidating the abiotic and biotic drivers of diversity within ecological communities. We examined the relationships among taxonomic and genetic metrics of diversity in freshwater mussels (Bivalvia: Unionidae), an ecologically important and species‐rich group in the southeastern United States. Using quantitative community surveys and reduced‐representation genome sequencing across 22 sites in seven rivers and two river basins, we surveyed 68 mussel species and sequenced 23 of these species to characterize intrapopulation genetic variation. We tested for the presence of species diversity–abundance correlations (i.e. the more‐individuals hypothesis, MIH), species‐genetic diversity correlations (SGDCs) and abundance‐genetic diversity correlations (AGDCs) across all sites to evaluate relationships between different metrics of diversity. Sites with greater cumulative multispecies density (a standardized metric of abundance) had a greater number of species, consistent with the MIH hypothesis. Intrapopulation genetic diversity was strongly associated with the density of most species, indicating the presence of AGDCs. However, there was no consistent evidence for SGDCs. Although sites with greater overall densities of mussels had greater species richness, sites with higher genetic diversity did not always exhibit positive correlations with species richness, suggesting that there are spatial and evolutionary scales at which the processes influencing community‐level diversity and intraspecific diversity differ. Our work reveals the importance of local abundance as indicator (and possibly a driver) of intrapopulation genetic diversity.

Broad-scale benthic habitat classification of the South Atlantic - Kirsty A. McQuaid; Amelia E.H. Bridges; Kerry L. Howell; Tiago B.R. Gandra; Vitor de Souza; Jock C. Currie; Oliver T. Hogg; Tabitha R.R. Pearman; James B. Bell; Lara J. Atkinson; Diane Baum; Jarbas Bonetti; et al. (Progress in Oceanography, 2023)

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

The Role of Satellite Telemetry Data in 21st Century Conservation of Polar Bears (Ursus maritimus) - Kristin L. Laidre; George M. Durner; Nicholas J. Lunn; Eric V. Regehr; Todd C. Atwood; Karyn D. Rode; Jon Aars; Heli Routti; Øystein Wiig; Markus Dyck; Evan S. Richardson; Stephen Atkinson; et al. (Frontiers in Marine Science, 2022)
Satellite telemetry (ST) has played a critical role in the management and conservation of polar bears ( Ursus maritimus ) over the last 50 years. ST data provide biological information relevant to subpopulation delineation, movements, habitat use, maternal denning, health, human-bear interactions, and accurate estimates of vital rates and abundance. Given that polar bears are distributed at low densities over vast and remote habitats, much of the information provided by ST data cannot be collected by other means. Obtaining ST data for polar bears requires chemical immobilization and application of a tracking device. Although immobilization has not been found to have negative effects beyond a several-day reduction in activity, over the last few decades opposition to immobilization and deployment of satellite-linked radio collars has resulted in a lack of current ST data in many of the 19 recognized polar bear subpopulations. Here, we review the uses of ST data for polar bears and evaluate its role in addressing 21 st century conservation and management challenges, which include estimation of sustainable harvest rates, understanding the impacts of climate warming, delineating critical habitat, and assessing potential anthropogenic impacts from tourism, resource development and extraction. We found that in subpopulations where ST data have been consistently collected, information was available to estimate vital rates and subpopulation density, document the effects of sea-ice loss, and inform management related to subsistence harvest and regulatory requirements. In contrast, a lack of ST data in some subpopulations resulted in increased bias and uncertainty in ecological and demographic parameters, which has a range of negative consequences. As sea-ice loss due to climate warming continues, there is a greater need to monitor polar bear distribution, habitat use, abundance, and subpopulation connectivity. We conclude that continued collection of ST data will be critically important for polar bear management and conservation in the 21 st century and that the benefits of immobilizing small numbers of individual polar bears in order to deploy ST devices significantly outweigh the risks.

Evolutionary history drives aspects of stoichiometric niche variation and functional effects within a guild - Carla L. Atkinson; Brian C. van Ee; John M. Pfeiffer (Ecology, 2020)
Functional traits are characteristics of an organism that represents how it interacts with its environment and can influence the structure and function of ecosystems. Ecological stoichiometry provides a framework to understand ecosystem structure and function by modeling the coupled flow of elements (e.g. carbon [C], nitrogen [N], phosphorus [P]) between consumers and their environment. Animals tend to be homeostatic in their nutrient requirements and preferentially sequester the element in shortest supply relative to demand, and release relatively more of the element in excess. Tissue stoichiometry is an important functional trait that allows for predictions among the elemental composition of animals, their diet, and their waste products, with important effects on the cycling and availability of nutrients in ecosystems. Here, we examined the tissue stoichiometric niches (C:N:P) and nutrient recycling stoichiometries (N:P) of several filter‐feeding freshwater mussels in the subfamily Ambleminae. Despite occupying the same functional‐feeding group and being restricted to a single subfamily‐level radiation, we found that species occupied distinct stoichiometric niches and that these niches varied, in part, as a function of their evolutionary history. The relationship between phylogenetic divergence and functional divergence suggests that evolutionary processes may be shaping niche complementarity and resource partitioning. Tissue and excretion stoichiometry were negatively correlated as predicted by stoichiometric theory. When scaled to the community, higher species richness and phylogenetic diversity resulted in greater functional evenness and reduced functional dispersion. Filter‐feeding bivalves are an ecologically important guild in freshwater ecosystems globally, and our study provides a more nuanced view of the stoichiometric niches and ecological functions performed by this phylogenetically and ecologically diverse assemblage.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Renewable energy development threatens many globally important biodiversity areas - Jose A. Rehbein; James E. M. Watson; Joe L. Lane; Laura J. Sonter; Oscar Venter; Scott C. Atkinson; James R. Allan (Global Change Biology, 2020)
Transitioning from fossil fuels to renewable energy is fundamental for halting anthropogenic climate change. However, renewable energy facilities can be land‐use intensive and impact conservation areas, and little attention has been given to whether the aggregated effect of energy transitions poses a substantial threat to global biodiversity. Here, we assess the extent of current and likely future renewable energy infrastructure associated with onshore wind, hydropower and solar photovoltaic generation, within three important conservation areas: protected areas (PAs), Key Biodiversity Areas (KBAs) and Earth's remaining wilderness. We identified 2,206 fully operational renewable energy facilities within the boundaries of these conservation areas, with another 922 facilities under development. Combined, these facilities span and are degrading 886 PAs, 749 KBAs and 40 distinct wilderness areas. Two trends are particularly concerning. First, while the majority of historical overlap occurs in Western Europe, the renewable electricity facilities under development increasingly overlap with conservation areas in Southeast Asia, a globally important region for biodiversity. Second, this next wave of renewable energy infrastructure represents a ~30% increase in the number of PAs and KBAs impacted and could increase the number of compromised wilderness areas by ~60%. If the world continues to rapidly transition towards renewable energy these areas will face increasing pressure to allow infrastructure expansion. Coordinated planning of renewable energy expansion and biodiversity conservation is essential to avoid conflicts that compromise their respective objectives.

India’s contribution to mitigating the impacts of climate change through vegetation management - J. Dash; M. D. Behera; C. Jeganathan; C. S. Jha; S. Sharma; R. Lucas; A. A. Khuroo; A. Harris; P. M. Atkinson; D. S. Boyd; C. P. Singh; M. P. Kale; et al. (Tropical Ecology, 2020)

Nutrient recycling by insect and fish communities in high-elevation tropical streams - Carla L. Atkinson; Alexander V. Alexiades; Keeley L. MacNeill; Andrea C. Encalada; Steve A. Thomas; Alexander S. Flecker (Hydrobiologia, 2019)

Diet of northern sea otters ( Enhydra lutris kenyoni ) from Icy Strait, Alaska, based on stomach contents analysis - Kristin L. Brown; Shannon Atkinson; Kierstin B. Keller; Heidi C. Pearson (Marine Mammal Science, 2019)

Biomass distribution of fishes and mussels mediates spatial and temporal heterogeneity in nutrient cycling in streams - Garrett W. Hopper; Keith B. Gido; Caryn C. Vaughn; Thomas B. Parr; Traci G. Popejoy; Carla L. Atkinson; Kiza K. Gates (Oecologia, 2018)

Determinants of food resource assimilation by stream insects along a tropical elevation gradient - Carla L. Atkinson; Andrea C. Encalada; Amanda T. Rugenski; Steve A. Thomas; Andrea Landeira-Dabarca; N. LeRoy Poff; Alexander S. Flecker (Oecologia, 2018)

Consumer Aggregations Drive Nutrient Dynamics and Ecosystem Metabolism in Nutrient-Limited Systems - Carla L. Atkinson; Brandon J. Sansom; Caryn C. Vaughn; Kenneth J. Forshay (Ecosystems, 2018)

Long-term change in epibenthic assemblages at the Prince Edward Islands: a comparison between 1988 and 2013 - C. E. O. von der Meden; L. J. Atkinson; G. M. Branch; S. Asdar; I. J. Ansorge; M. van den Berg (Polar Biology, 2017)

Potential cardiovascular adverse events when phenylephrine is combined with paracetamol: simulation and narrative review - Hartley C. Atkinson; Amanda L. Potts; Brian J. Anderson (European Journal of Clinical Pharmacology, 2015)

Erratum to: Increased bioavailability of phenylephrine by co-administration of acetaminophen: results of four open-label, crossover pharmacokinetic trials in healthy volunteers - Hartley C. Atkinson; Ioana Stanescu; Isam I. Salem; Amanda L. Potts; Brian J. Anderson (European Journal of Clinical Pharmacology, 2015)

Increased bioavailability of phenylephrine by co-administration of acetaminophen: results of four open-label, crossover pharmacokinetic trials in healthy volunteers - Hartley C. Atkinson; Ioana Stanescu; Isam I. Salem; Amanda L. Potts; Brian J. Anderson (European Journal of Clinical Pharmacology, 2015)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Tracing Consumer-Derived Nitrogen in Riverine Food Webs - Carla L. Atkinson; Jeffrey F. Kelly; Caryn C. Vaughn (Ecosystems, 2014)

Cooperation between scientists, NGOs and industry in support of sustainable fisheries: the South African hake Merluccius spp. trawl fishery experience a - J. G. Field; C. G. Attwood; A. Jarre; K. Sink; L. J. Atkinson; S. Petersen (Journal of Fish Biology, 2013)
This paper examines the increasingly close interaction between natural and social scientists, non‐governmental organizations (NGO) and industry, in pursuit of responsible ecosystem‐based management of fisheries. South Africa has committed to implementing an ecosystem approach to fisheries management. Management advice stems from multi‐stakeholder representation on government‐led scientific and management working groups. In the hake Merluccius capensis and Merluccius paradoxus fishery, the primary management measure is an annual total allowable catch ( TAC ), the level of which is calculated using a management procedure ( MP ) that is revised approximately every 4 years. Revision of the MP is a consultative process involving most stakeholders, and is based on simulation modelling of projected probable scenarios of resource and fishery dynamics under various management options. NGOs , such as the Worldwide Fund for Nature in South Africa (WWF‐SA), have played an important role in influencing consumers, the fishing industry and government to develop responsible fishing practices that minimize damage to marine ecosystems. Cooperation between industry, government and scientists has helped to improve sustainability and facilitated the meeting of market‐based incentives for more responsible fisheries. Research includes ecosystem modelling, spatial analysis and ecosystem risk assessment with increasing research focus on social and economic aspects of the fishery. A four‐year cooperative experiment to quantify the effect of trawling on benthic community structure is being planned. The food requirements of top predators still need to be included in the TAC ‐setting formulae and more social and economic research is needed. This paper also demonstrates how NGO initiatives such as Marine Stewardship Council certification and the Southern African Sustainable Seafood Initiative, a traffic light system of classifying seafood for consumers, have contributed to responsible fishing practices, increased ecosystem research and public awareness. This fishery appears to have a good future, provided that the monitoring, control and surveillance systems continue to function, TACs remain within ecologically sustainable limits and the effective collaboration between government, industry, scientists and NGOs continues to drive positive change.

Aggregated filter‐feeding consumers alter nutrient limitation: consequences for ecosystem and community dynamics - Carla L. Atkinson; Caryn C. Vaughn; Kenneth J. Forshay; Joshua T. Cooper (Ecology, 2013)
Nutrient cycling is a key process linking organisms in ecosystems. This is especially apparent in stream environments in which nutrients are taken up readily and cycled through the system in a downstream trajectory. Ecological stoichiometry predicts that biogeochemical cycles of different elements are interdependent because the organisms that drive these cycles require fixed ratios of nutrients. There is growing recognition that animals play an important role in biogeochemical cycling across ecosystems. In particular, dense aggregations of consumers can create biogeochemical hotspots in aquatic ecosystems via nutrient translocation. We predicted that filter‐feeding freshwater mussels, which occur as speciose, high‐biomass aggregates, would create biogeochemical hotspots in streams by altering nutrient limitation and algal dynamics. In a field study, we manipulated nitrogen and phosphorus using nutrient‐diffusing substrates in areas with high and low mussel abundance, recorded algal growth and community composition, and determined in situ mussel excretion stoichiometry at 18 sites in three rivers (Kiamichi, Little, and Mountain Fork Rivers, south‐central United States). Our results indicate that mussels greatly influence ecosystem processes by modifying the nutrients that limit primary productivity. Sites without mussels were N‐limited with ∼26% higher relative abundances of N‐fixing blue‐green algae, while sites with high mussel densities were co‐limited (N and P) and dominated by diatoms. These results corroborated the results of our excretion experiments; our path analysis indicated that mussel excretion has a strong influence on stream water column N:P. Due to the high N:P of mussel excretion, strict N‐limitation was alleviated, and the system switched to being co‐limited by both N and P. This shows that translocation of nutrients by mussel aggregations is important to nutrient dynamics and algal species composition in these rivers. Our study highlights the importance of consumers and this imperiled faunal group on nutrient cycling and community dynamics in aquatic ecosystems.

Recombinant monoclonal antibody yield in transgenic tobacco plants is affected by the wounding response via an ethylene dependent mechanism - Sally Hassan; Richard Colgan; Mathew J. Paul; Christopher J. Atkinson; Amy L. Sexton; Craig J. van Dolleweerd; Eli Keshavarz-Moore; Julian K-C. Ma (Transgenic Research, 2012)

Atlantic transport variability at 25° N in six hydrographic sections - C. P. Atkinson; H. L. Bryden; S. A. Cunningham; B. A. King (Ocean Science, 2012)
In January and February 2010, a sixth transatlantic hydrographic section was completed across 25° N, extending the hydrographic record at this latitude to over half a century. In combination with continuous transport measurements made since 2004 at 26.5° N by the Rapid-WATCH project, we reassess transport variability in the 25° N hydrographic record. Past studies of transport variability at this latitude have assumed transport estimates from each hydrographic section to represent annual average conditions. In this study the uncertainty in this assumption is assessed through use of Rapid-WATCH observations to quantify sub-seasonal and seasonal transport variability. Whilst in the upper-ocean no significant interannual or decadal transport variability are identified in the hydrographic record, in the deep ocean transport variability in both depth and potential temperature classes suggests some interannual or decadal variability may have occurred. This is particularly striking in the lower North Atlantic Deep Water where southward transports prior to 1998 were greater than recent transports by several Sverdrups. Whilst a cooling and freshening of Denmark Straits Overflow Water has occurred which is coincident with these transport changes, these water mass changes appear to be density compensated. Transport changes are the result of changing velocity shear in the vicinity of the Deep Western Boundary Current.

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

On the seasonal cycles and variability of Florida Straits, Ekman and Sverdrup transports at 26° N in the Atlantic Ocean - C. P. Atkinson; H. L. Bryden; J. J-M. Hirschi; T. Kanzow (Ocean Science, 2010)
Since April 2004 the RAPID array has made continuous measurements of the Atlantic Meridional Overturning Circulation (AMOC) at 26° N. Two key components of this system are Ekman transport zonally integrated across 26° N and western boundary current transport in the Florida Straits. Whilst measurements of the AMOC as a whole are somewhat in their infancy, this study investigates what useful information can be extracted on the variability of the Ekman and Florida Straits transports using the decadal timeseries already available. Analysis is also presented for Sverdrup transports zonally integrated across 26° N. The seasonal cycles of Florida Straits, Ekman and Sverdrup transports are quantified at 26° N using harmonic analysis of annual and semi-annual constituents. Whilst Sverdrup transport shows clear semi-annual periodicity, calculations of seasonal Florida Straits and Ekman transports show substantial interannual variability due to contamination by variability at non-seasonal frequencies; the mean seasonal cycle for these transports only emerges from decadal length observations. The Florida Straits and Ekman mean seasonal cycles project on the AMOC with a combined peak-to-peak seasonal range of 3.5 Sv. The combined seasonal range for heat transport is 0.40 PW. The Florida Straits seasonal cycle possesses a smooth annual periodicity in contrast with previous studies suggesting a more asymmetric structure. No clear evidence is found to support significant changes in the Florida Straits seasonal cycle at sub-decadal periods. Whilst evidence of wind driven Florida Straits transport variability is seen at sub-seasonal and annual periods, a model run from the 1/4° eddy-permitting ocean model NEMO is used to identify an important contribution from internal oceanic variability at sub-annual and interannual periods. The Ekman transport seasonal cycle possesses less symmetric structure, due in part to different seasonal transport regimes east and west of 50 to 60° W. Around 60% of non-seasonal Ekman transport variability occurs in phase section-wide at 26° N and is related to the NAO, whilst Sverdrup transport variability is more difficult to decompose.

The Challenges of Dewatering at the Victor Diamond Mine in Northern Ontario, Canada - L. C. Atkinson; P. G. Keeping; J. C. Wright; Houmao Liu (Mine Water and the Environment, 2010)

Optimisation of contained Nicotiana tabacum cultivation for the production of recombinant protein pharmaceuticals - Richard Colgan; Christopher J. Atkinson; Matthew Paul; Sally Hassan; Pascal M. W. Drake; Amy L. Sexton; Simon Santa-Cruz; David James; Keith Hamp; Colin Gutteridge; Julian K-C. Ma (Transgenic Research, 2010)

Associations between endogenous sex hormone levels and mammographic and bone densities in premenopausal women - Mellissa Yong; Charlotte Atkinson; Katherine M. Newton; Erin J. Aiello Bowles; Frank Z. Stanczyk; Kim C. Westerlind; Victoria L. Holt; Stephen M. Schwartz; Wendy M. Leisenring; Johanna W. Lampe (Cancer Causes & Control, 2009)

Production of transgenic pineapple (Ananas cosmos (L.) Merr.) plants via adventitious bud regeneration - M.-L. Wang; G. Uruu; L. Xiong; X. He; C. Nagai; K. T. Cheah; J. S. Hu; G.-L. Nan; B. S. Sipes; H. J. Atkinson; P. H. Moore; K. G. Rohrbach; et al. (In Vitro Cellular & Developmental Biology - Plant, 2009)

Natural selection of the major histocompatibility complex ( Mhc ) in Hawaiian honeycreepers (Drepanidinae) - SUSAN I. JARVI; CHERYL L. TARR; CARL E. MCINTOSH; CARTER T. ATKINSON; ROBERT C. FLEISCHER (Molecular Ecology, 2004)
The native Hawaiian honeycreepers represent a classic example of adaptive radiation and speciation, but currently face one the highest extinction rates in the world. Although multiple factors have likely influenced the fate of Hawaiian birds, the relatively recent introduction of avian malaria is thought to be a major factor limiting honeycreeper distribution and abundance. We have initiated genetic analyses of class II β chain Mhc genes in four species of honeycreepers using methods that eliminate the possibility of sequencing mosaic variants formed by cloning heteroduplexed polymerase chain reaction products. Phylogenetic analyses group the honeycreeper Mhc sequences into two distinct clusters. Variation within one cluster is high, with d N > d S and levels of diversity similar to other studies of Mhc ( B system) genes in birds. The second cluster is nearly invariant and includes sequences from honeycreepers (Fringillidae), a sparrow (Emberizidae) and a blackbird (Emberizidae). This highly conserved cluster appears reminiscent of the independently segregating Rfp‐Y system of genes defined in chickens. The notion that balancing selection operates at the Mhc in the honeycreepers is supported by transpecies polymorphism and strikingly high d N / d S ratios at codons putatively involved in peptide interaction. Mitochondrial DNA control region sequences were invariant in the i’iwi, but were highly variable in the ‘amakihi. By contrast, levels of variability of class II β chain Mhc sequence codons that are hypothesized to be directly involved in peptide interactions appear comparable between i’iwi and ‘amakihi. In the i’iwi, natural selection may have maintained variation within the Mhc , even in the face of what appears to a genetic bottleneck.

Habitat selection in whiting - C. J. L. Atkinson; M. Bergmann; M. J. Kaiser (Journal of Fish Biology, 2004)
Given a choice of habitats in a laboratory experiment, whiting Merlangius merlangus preferentially spent most time over sand, then gravel and least time over a habitat with emergent structures. The introduction of a predator stimulus increased the preference for the sand habitat for large whiting, whereas small whiting had an increased preference for the habitat with emergent structures.

Evaluation of the Best disease gene in patients with age-related macular degeneration and other maculopathies - R. Allikmets; Johanna M. Seddon; Paul S. Bernstein; A. Hutchinson; Andrew Atkinson; Sanjay Sharma; Bernard Gerrard; W. Li; Michael L. Metzker; Claes Wadelius; C. Thomas Caskey; Michael Dean; et al. (Human Genetics, 1999)

A LARGE PLACENTA ENCOUNTERED IN THE HAWAIIAN WINTER GROUNDS OF THE HUMPBACK WHALE, MEGAPTERA NOVAEANGLIAE - L. E. Silvers; S. Atkinson; M. Iwasa; C. Combelles; D. R. Salden (Marine Mammal Science, 1997)